Event based and time based prospective memory in Parkinson's disease. Issue 6 (1st June 2003) - Katai, S; Maruyama, T; Hashimoto, T; Ikeda, S
Abstract : Background: Patients with Parkinson's disease have been reported to have retrospective memory impairment, while prospective memory, which is memory for actions to be performed in the future, has not yet been investigated. Objective: To investigate the prospective memory of patients with Parkinson's disease. Methods: Twenty Parkinson's disease patients and 20 age matched normal controls were given event based and time based prospective memory tasks. In the event based prospective memory task, the subject was asked to perform an action whenever particular words were presented. In the time based prospective memory task, the subject was asked to perform an action at certain times. Results: The Parkinson's disease patients were impaired on the event based prospective memory task but not on the time based prospective memory task. The impairment of the Parkinson's disease patients on the event based prospective memory task was not the result of their forgetting the content of the prospective memory instructions, but the result of their failure to retrieve it spontaneously when the target words appeared. Conclusions: These results suggest that event based prospective memory is impaired in patients with Parkinson's disease, presumably relating to frontal lobe dysfunction.